Exploring Linguistic Landscapes of Pesantren: Their Patterns and Functions - Kamal Yusuf; Ica Oktaviana; Nisrina Aulia Nisa; Nurjannah Nurjannah (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
This study investigates a language phenomenon known as Linguistic Landscape, which consists of linguistic signs that are widely used in public spaces, one of which is as exposed in pesantren. Pesantren has unique Islamic environment combines with religious atmosphere and Islamic education that convey information to the public. The aims of this study are to investigate the patterns of language use in the Linguistic Landscape and to identify the function of language use in the pesantren environment. The present study is a qualitative in nature. The sites of the research were pesantren Nurul Falah, Surabaya and pesantren Bahrul Ulum, Tambakberas, Jombang. The data was collected through documentation and direct observation. The research stages include data collection, data analysis, and drawing conclusion. The findings of this research revealed that the patterns of language used in the observed pesantren vary, including monolingual, bilingual, and multilingual signs. The use of language signs in the pesantren environment serves as signboard markers, warning signs, and information signs. The functions of Linguistic Landscape in pesantren surveyed demonstrate the use of informational and symbolic functions.